Designing a Sea Wave Simulator to Determine the Energy Potential of a Marine Wave Power Plant Using IMU GY-86 Sensor - Hendi Purnata; Sugeng Dwi Riyanto; Purwiyanto (Jurnal E-Komtek, 2022)
This study intended to create a sea wave simulator to find out the potential of ocean wave power plants. To achieve the objective, this study used two systems: generation and reading. Generation used a DC motor as a drive from sea waves, while readings employed an IMU-GY86 sensor for readings of altitude and energy potential generated. The result of this study is that air and air pressure affect the results of measuring the wave height of seawater. Air pressure is inversely proportional to the elevation of a place: the higher the area, the lower the air pressure. The highest potential energy density of seawater waves amounts to 2405.33 J/m2, and the lowest was 550.18 J/m2, with an average value of seawater wave density energy of 1342.41 J/m2.